Taxonomic and phylogenetic insights into novel Ascomycota from contaminated soils in Yunnan, China - Yasanthika, Erandi; Wanasinghe, Dhanushka N.; Ren, Guang-Cong; Karunarathna, Samantha C.; Tennakoon, Danushka S.; Monkai, Jutamart; Gui, Heng; Mortimer, Peter E.; Lumyong, Saisamorn; Hyde, Kevin D. (Phytotaxa, 2021)
Industrial soil contamination negatively affects flora and fauna in the soil. Nevertheless, some fungi have the ability to survive in such polluted soils. In this study, we isolated fungal strains from polluted soils in industrialized areas of Kunming City, Yunnan Province, China. Fungal strains underwent morphological observations, subjected to phylogenetic analyses and subsequently described using morphological characterizations and multigene phylogenetic inferences. The molecular data of partial nuclear ribosomal DNA (rDNA) (LSU, SSU and ITS) and protein-coding genes (tef1-α, rpb2 and btub) were used to resolve the phylogeny of newly generated sequences. Maximum likelihood and Bayesian inference analyses were constructed to clarify phylogenetic affinities. Based on the biphasic approach of incorporating morphology and molecular data, we introduce one new species, Juxtiphoma yunnanensis sp. nov. (Didymellaceae, Pleosporales), two new records viz. Lecanicillium dimorphum (J.D. Chen) Zare & W. Gams (Cordycipitaceae, Hypocreales) and Scopulariopsis brevicaulis (Sacc.) Bainier (Microascaceae, Microascales) inhabit polluted soils in China.